Optimization of Short Probe Linear Frequency Modulated Signal Parameters - Włodzimierz POGRIBNY; Tadeusz LESZCZYŃSKI (Archives of Acoustics, 2013)
In many physical experiments, linear frequency modulated (LFM) signals are widely used to probe objects in different environments, from outer-space to underwater. These signals allow a significant improvement in measurement resolution, even when the observation distance is great. For example, using LFM probe signals in underwater investigations enables discovery of even small objects covered by bottom sediments.